EFFECT OF THE FUNCTIONAL CONDITION ON THE FREQUENCY OF INTRAOPERATIVE CRITICAL INCIDENTS IN PATIENTS WITH ACUTE COLONIC OBSTRUCTION - Andrei V. Stakanov; Tat’yana S. Musaeva; Vladislav V. Golubtsov; Aleksei E. Muronov (Кубанский научный медицинский вестник, 2019)
The aim of this study was to identify the distinctive features of the course of anesthesia and the structure of critical incidents (CI) in patients with various functional states (FS) during surgical interventions aimed at eliminating acute colonic obstruction.Materials and methods. 146 patients having undergone emergency surgical interventions aimed at eliminating acute colonic obstruction were examined. On the basis of the constant potential (CP) value, 3 groups were identified. Group 1 (n=66) was characterized by the CP value of -30 mV and below (FS subcompensation). Group 2 (n=44) included patients with the average negative CP values from -15 to -29.9 mV (FS compensation). Group 3 (n=36) comprised patients with the low negative and positive CP values of -14.9 mV and above (FS decompensation). The connection of FS with the frequency of the CI development was studied. The recorded CI included hemodynamic: hypotension — hypertension — bradycardia — arrhythmia — tachycardia; respiratory: hypoxemia — hypercapnia — the need for a prolonged mechanical ventilation of lungs in the postoperative period; metabolic: hypothermia — retarded recovery of the neuromuscular conductivity — delayed postoperative awakening.Results. CI occurrence is found to be different in patients with different FS. Hemodynamic CIs were noted in all the studied groups; however, their proportion in patients with high and low negative and positive CP values was significantly higher. Their formation was accompanied by violations of the adequate course of anesthesia, namely, the hypokinetic state of the blood circulation and aerobic metabolism. In addition, this group showed an increase in the frequency of a slow recovery of the neuromuscular conduction and delayed postoperative awakening.Conclusion. The most adequate course of anesthesia has been observed in patients with moderate negative CP values.Conflict of interest: the authors declare no conflict of interest